Non-perturbative terahertz high-harmonic generation in the three-dimensional Dirac semimetal Cd3As2 - Sergey Kovalev (Nature Portfolio, 2020)
The mechanism and scaling of high harmonic generation in solids is a highly compelling ongoing area of research. Here the authors show a non-perturbative behavior of HHG in terahertz regime from 3D Dirac semimetal, Cd3As2, at room temperature, and reveal the underlying nonlinear kinetics.